Knowledge and Awareness of Masks and N95 Respirators Used for COVID-19 Prevention Among Chemical Engineering Students at Al-Balqa Applied University, Jordan - Hudaib, Banan; Al-shawabkeh, Ali F.; Hudaib, Fadia (Frontiers in Public Health, 2022)
On 11th March, the World Health Organization declared COVID-19 as a global pandemic; the rapid and extended spread of the COVID-19 pandemic has become a significant cause of concern for university study. This study investigated the knowledge of chemical engineering students in Al Balqa Applied University in Jordan about respiratory protective measures against COVID-19. A cross-sectional study was developed using a multi-stage random sampling technique conducted from 21st to 28th April 2020. The data collected through an online questionnaire distributed to the chemical engineering students of Al Balqa applied university. The data were analyzed statistically using the SPSS program. The questionnaire consisted of two parts: the first measured the student's general knowledge about the COVID-19 pandemic, while the second focused on the respiratory protection methods against COVID-19; it was structured to assess student's knowledge about the suitable types of masks and respirators used in the COVID-19 prevention, their detailed mechanism of action and filtration process type, production materials, and finally how student's knowledge affects choosing a proper preventive method. The study found moderate awareness among engineering students about COVID-19 causative agent, effective preventive masks/respirators used, and the mask's viral blockage mechanisms. About half of the respondents pointed to the correct mask type and its working mechanism, and 49.7 % of respondents knew the best protective mask, i.e., N95 mask. In contrast, about two-thirds of the students believed that a surgical mask is the best protective mask. The study also showed differences in knowledge between different academic years; the knowledge about respirators, masks, and their action mechanism among senior students in the last three academic years was better than the younger students. On the other hand, the study showed a lack of awareness of the most suitable mask types used in pandemic and the appropriately using method. The study found that chemical engineering students in Al Balqa university were moderately knowledgeable regarding Covid 19 respiratory preventive methods; these results provided us with an overview of the knowledge level in the student's community. Therefore, efforts are needed to improve public awareness through comprehensive educational campaigns to increase students' knowledge, attitude, and practice.